The Effect Of Skills, Work Experience, Andwork Commitment On Performance Employees of PT. Mitsubishi Bengkulu City Branch (Dealer Employee Case Study) - Raja Lutfi Abdillah; Yulius Wahyu Setiadi (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the Effect of Skills, Work Experience, and Work Commitment on Employee Performance at PT. Mitsubishi Bengkulu City Branch. This type of research uses quantitative methods, the object of this research is employees of PT. Mitsubishi Bengkulu City Branch with the sampling method, namely the total sampling technique. The number of respondents in this study were 50 people. In this study the authors used data collection methods by means of observation, interviews and distributing questionnaires or questionnaires. By using data analysis techniques using Instrument Tests namely Validity Tests and Reliability Tests, Classical Assumption Tests namely Multicollinearity Tests, Normality Tests. and Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Coefficient of Determination (R2), and Hypothesis Test, namely t test and f test. The results of this study can be concluded that partially and simultaneously work skills have no significant effect on employee performance at PT. Mitsubishi Bengkulu City Branch, partially and simultaneously Work Experience has a significant effect on Employee Performance at PT. Mitsubishi Bengkulu City Branch, and Work Commitment has a significant effect partially simultaneously on Employee Performance at PT. .Mitsubishi Bengkulu City Branch.